Microphase Separation of Block Copolymer Thin Films - Zhang, Jilin; Yu, Xinhong; Yang, Ping; Peng, Juan; Luo, Chunxia; Huang, Weihuan; Han, Yanchun (Macromolecular rapid communications., 2010)
Today, high‐ordered micro‐ and nano‐patterned surfaces are widely used in many areas, such as in the preparation of super‐thin dielectric films, photonic crystals, antireflective films, super‐non‐wetting surfaces, bio‐compatible surfaces and microelectric devices. Considering the critical fabrication conditions and the irreducible high cost of the photolithography technique in patterning nano‐scale structures (<100 nm), the development of other micro‐ and nano‐patterning techniques that can be used to fabricate long‐range ordered features – especially nanoscale arrays – is a promising subject in surface science. In contrast to the traditional photolithography patterning technique, block copolymers can spontaneously phase separate into arrays of periodic patterns with length‐scales of 10–50 nm, which provides an efficient pathway to pattern nanoscale features. Today, preparing long‐range ordered arrays by block copolymer microphase separation is one of the most promising techniques for the fabrication of nanoscale arrays, not only being a simple process but also having a lower cost than traditional methods. In this feature article, we first summarize the many techniques developed to induce ordering in the microphase separation of the block copolymer thin films. Then, evolution, order–order transitions and reversible switching microdomains are considered, since they are very important in the ordered engineering of microphase separation of the block copolymer thin films. Finally, the outlook of this research area will be given. Preparing long‐range ordered arrays by block copolymer microphase separation is one of the most promising techniques for the fabrication of nanoscale arrays. We summarize the many techniques developed to induce ordering in the microphase separation of the block copolymer thin films. Evolution, order–order transitions and reversible switching microdomains are also considered, since they are very important in the ordered engineering of microphase separation of the block copolymer thin films. The outlook for this research area is discussed.